COMPARISON BETWEEN REMOVABLE AND FIXED ORTHODONTIC RETAINERS - Goenharto, Sianiwati; Rusdiana, Elly; Khairyyah, Ida Nurul (Faculty of Vocational Studies, Universitas Airlangga, 2017)
Background: There are two kinds of retainers: removable retainer and fixed retainer. Removable retainer is an orthodontic retainer which can be inserted and removed by the patient, whereas fixed retainer is bonded permanently on teeth, it cannot be removed by the patient. It is important to know which retainer that most effective based on the existing case. Purpose: To identify the comparison between removable and fixed retainers in orthodontic treatment. Review: Hawley retainer, Beggs retainer, clip on retainer, Kesling'stooth positioners and invisible retainer are removable retainers whereas fixed retainers include banded retainer, bonded retainer and band & spur type retainer. Comparison between removable and fix retainer can be evaluated from several aspects such as: cost, aesthetics, fabrication process, durability, occlusion, hygiene and convenience of use. Conclusion: Whether removable or fixed retainers can be effectively used to prevent relapse post orthodontic treatment depending onthe existing case.